Discourse in Dialogue Reflections in Fundamental Philosophical Theology. - Rossi, Pat F. (Newcastle upon Tyne : Cambridge Scholars Publishing, 2012)
Discourse in Dialogue: Reflections in Fundamental Philosophical Theology is a project which considers fundamental theological and philosophical perspectives in Catholic-Christian theology. This project adumbrates a number of specifically intellectual themes, namely philosophical and theological in character, which pertain to the Catholic-Christian tradition. These themes include a study of the following: the interrelationship of philosophy and theology; theological method and pluralism; the i...
Table of contents; preface; chapter one -- pascendi: philosophical and theological perspectives; chapter two -- aeterni patris: unitary method evidence of pluralism; chapter three -- l'interpretation de la bible dans l'eglise: interpretive principles and methods in catholic theological thought; chapter four -- gaudium et spes: reaffirmation of christian humanism; chapter five -- redemptor hominis: the incarnational mystery and the question of human transcendence; chapter six -- fides et ratio: faith informing understanding; index
Description based upon print version of record.
Keywords: Globalization; Religion and sociology; Religion; Catholic Church -- Doctrines -- History; Philosophical theology; RELIGION / Christian Theology / Systematic; RELIGION / Christianity / General; Electronic books